Ship Design and Maintenance Computer Program (Icebreaker Propulsion System Simulation. Diesel - Electric) - Lewis, Jack W (1968)
This program solves numerically the set of simultaneous non-linear differential equations which describe the dynamic behavior of the complete propulsion system (including vessel dynamics) of a diesel-electric icebreaker during maneuvering. The program also contains a means of subjecting the propeller to ice impact loadings of the user's making. At the option of the user, input data can readily be printed for documentation purposes and output data can be plotted. (Author)